Turbinate hypertrophy in children with allergic rhinitis: clinical relevance - Ciprandi, Giorgio; Tosca, Maria Angela; Gallo, Fabio; Passali, Giulio Cesare; Ameli, Franco (Acta Biomedica Atenei Parmensis, 2020)
Allergic rhinitis (AR) is the most common immune-mediated disorder in childhood as it may affect up to 40% of children. Turbinate hypertrophy (TH) is an important sign as reliably predicts AR both in children and adults. Consistently, nasal obstruction is a very common symptom in AR patients and is closely linked with turbinate hypertrophy. This study investigated 544 (304 males) children with AR to define factors associated with TH. TH was diagnosed in 438 (80.81%) AR children. The multivariate analysis demonstrated a significant association between age, male gender, and recurrent acute otitis media (RAOM), and TH (p-values: 0.0219, <0.0001, and 0.0003, respectively; OR 0.87, 3.97, and 0.22 respectively). In conclusion, this real-life study showed that TH was very frequent in children with AR and age, male gender, and RAOM were significantly associated with TH.